Prevalence and Risk Factors of Work-related Musculoskeletal Disorders Among Nurses: A Cross-Sectional Study in Benghazi, Libya - Alalagy, Sofian; Altaeb, Salem; Saffour, Moner (AlQalam Journal of Medical and Applied Sciences, 2025)
This study looks into the prevalence of work-related musculoskeletal disorders among nurses in Benghazi, Libya, and analyzes associated risk factors. A cross-sectional survey was done using the Nordic Musculoskeletal Questionnaire (NMQ), involving 215 registered nurses from several polyclinics in Benghazi. The questionnaire investigated the prevalence and functional impact of work-related musculoskeletal disorders, as well as demographic and occupational characteristics. Inclusion criteria: registered nurses who had worked for at least one year. Exclusion criteria: those with under one year of experience or pre-existing musculoskeletal diseases. Data were analyzed using SPSS version 24 with chi-square tests and logistic regression. Significance was set at p < 0.05. The mean age of participants was 43.66 (±7.24) years, with females comprising 94.9% (n=204). Participants worked an average of 19.28 (±8.84) hours per week and had a mean work experience of 19.36 (±9) years. Mean BMI was 29.39 (±5.29) kg/m². The results indicate high prevalence (92.1%), with common pain sites being lower back (68.8%), neck (52.6%), and knee (48.4%). Functional limitations due to low back pain affected 41.9%. Differences across age groups were not statistically significant (p = 0.152). No associations were found between BMI and knee pain (p=0.597) or years of experience and neck pain (p=0.720). However, a strong association was found between weekly working hours and low back pain (p = 0.007). Logistic regression revealed no significant associations, though a trend was noted for BMI (p = 0.062).